2020
DOI: 10.2147/hiv.s274764
|View full text |Cite
|
Sign up to set email alerts
|

<p>Minimum Acceptable Diet and Associated Factors Among HIV-Exposed Children Aged 6–24 Months in Debre Tabor Town, Ethiopia</p>

Abstract: Introduction Minimum acceptable diet is a composite indicator of minimum dietary diversity and minimum meal frequency. World Health Organization’s newborn child feeding and HIV guidelines suggestbeginning complementary nourishments at six months, and breastfeeding for HIV-exposed children. HIV infected mothers may be more sensitive on feeding practices to protect their children from contracting the disease. On the other hand, HIV infection is associated with higher risk food insecurity which may a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 5 publications
0
6
1
1
Order By: Relevance
“…Regarding meal frequency this study found that more than half (55.1%) of infant and young children aged 6–23 months in Ethiopia received the recommended minimum meal frequency. This finding was lower than study studies conducted in Debre Tabor Town (76%) [ 31 ], Dabat District (72.2%) [ 37 ], Wolaita Sodo town (68.9%) [ 38 ], Bale Zone (68.4%) [ 35 ]. However, the finding was slightly higher than a study from Afar Region (43.8%) [ 22 ] and Dangila district (50.4%) [ 39 ].…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Regarding meal frequency this study found that more than half (55.1%) of infant and young children aged 6–23 months in Ethiopia received the recommended minimum meal frequency. This finding was lower than study studies conducted in Debre Tabor Town (76%) [ 31 ], Dabat District (72.2%) [ 37 ], Wolaita Sodo town (68.9%) [ 38 ], Bale Zone (68.4%) [ 35 ]. However, the finding was slightly higher than a study from Afar Region (43.8%) [ 22 ] and Dangila district (50.4%) [ 39 ].…”
Section: Discussioncontrasting
confidence: 56%
“…This finding was nearly similar with study conducted in Sinan district, Southern Ethiopia, 13% [ 30 ]. However, it was by far lower than studies conducted in Debre Tabor town, Northern Ethiopia, 58.2% [ 31 ], Addis Ababa, 59.9% [ 32 ], in Bench Maji Zone, 38% [ 33 ] and Gorche district Southern Ethiopia, 29.9% [ 34 ], and Bale zone, Southern Oromia region 28.5% [ 35 ]. These discrepancy might be due to small sample size and urban setting in the previous studies.…”
Section: Discussionmentioning
confidence: 88%
“…The present study found that birthing in a health facility was significantly associated with higher odds of minimum acceptable diet feeding practice and this finding is supported by a study done in west Africa [ 24 ]. This might be as institutional delivery increases exposure to health information and improves mothers’ knowledge about infant and young child feeding [ 34 ]. In this study, children from a household who used traditional biomass as a source of fuel (wood, animal dug and others) had a lower chance to feed a minimum acceptable diet.…”
Section: Discussionmentioning
confidence: 99%
“…Children with mothers who did not work (63.7%) were higher in MAD fulfillment than children with mothers who worked (58.8%), meaning that the proportion of minimum diet for children with working mothers was lower than children with mothers who did not work. Children whose mothers did not have a workload had a higher likelihood of receiving proper complementary eating, and thus better MAD fulfillment, than children whose mothers did (Yisak et al 2020).…”
Section: Minimum Acceptable Diet and Its Associated Factorsmentioning
confidence: 93%